On the Cultural Revolution in Tibet : the Nyemo Incident of 1969 - Goldstein, Melvyn C. (University of California Press, 2009)
Among the conflicts to break out during the Cultural Revolution in Tibet, the most famous took place in the summer of 1969 in Nyemo, a county to the south and west of Lhasa. In this incident, hundreds of villagers formed a mob led by a young nun who was said to be possessed by a deity associated with the famous warrior-king Gesar. In their rampage the mob attacked, mutilated, and killed county officials and local villagers as well as People's Liberation Army troops. This groundbreaking book, the first on the Cultural Revolution in Tibet, revisits the Nyemo Incident, which has long been romanti.